Financial stability in dollarized economies - Gulde, Anne-Marie [et al.] (IMF WashingtonUS, 2004)
Examines the specific risks for financial soundness associated with dollarization. Discusses approaches to stopping bank runs and stabilizing liquidity conditions in the wake of a banking crisis in a dollarized economy. Proposes measures to limit the risk of banking crises in dollarized-prone economies.